The Impact Of Work Environment And Employee Satisfaction On Organizational Success With A Humanism In Management - Asmara, Maisa Azizah; Budiwati, Neti; Abdurahman, Fairuz Rifqi; Maulana, Yono; Purwanto, Heri (Jurnal Ekonomi, 2024)
Employee dissatisfaction and turnover pose significant challenges in Indonesia, with nearly 7.2 million individuals unemployed as of February 2024. This research explores the factors causing job dissatisfaction and strategies to enhance employee well-being and satisfaction. The study emphasizes the importance of a humanistic management approach that prioritizes individual dignity and well-being in creating a conducive work environment. Categorized as descriptive research with a quantitative approach, this study employs non-probability sampling using the purposive sampling method, with a sample size of 20 individuals. The research also applies multiple linear regression analysis methods, with data processed using IBM SPSS version 26.0. The research findings indicate that job satisfaction (X1) significantly affects organizational success (Y) at Arromanis Corner Store Bandung, while the work environment (X2) does not have a significant impact on organizational success (Y). Therefore, it can be concluded that the variables of job satisfaction (X1) collectively and significantly influence organizational success (Y) at Arromanis Corner Store Bandung.